The Effect of Population Growth, Income Distribution Inequality, and Poverty on Economic Growth during the Period 2003 to 2020 in the South Sulawesi - Hastuti, Diah Retno Dwi; Abd. Rahim; Ika Sulistyawaty Fitria (Bulletin of Economic Studies (BEST), 2023)
The population is one of the factors that can affect economic growth. The population that continues to increase can cause development problems such as inequality in income distribution and poverty. The population in South Sulawesi Province continues to increase, but this increase is not in line with fluctuating economic growth in South Sulawesi Province. This study aimed to determine the effect of population growth, income distribution inequality, and poverty on the economic growth of South Sulawesi Province. The type of data used is secondary data. In addition, this data uses time-series data from 2003 to 2020. This research uses a multiple linear regression model. The results show that population growth and poverty do not affect economic growth in South Sulawesi Province. At the same time, inequality in income distribution affects economic growth in South Sulawesi Province. Based on the research results, it is hoped that the South Sulawesi provincial government can provide jobs or further improve the population’s quality. The improvement in the quality of human resources is expected to increase economic growth. Thus, it can reduce poverty and reduce inequality.